Marketing analysis of multimodal transportation dynamics in logistics infrastructure. - Penev, Nikolay; Shyriaieva, Liudmyla; Legeza, Darya; Легеза, Дар’я Георгіївна; Merkulov, Mykola; Honcharova, Iryna (My University, 2024)
The basis of economic growth is the presence of a transport system that fully satisfies the needs of all participants in the economic process. The motivation for the study was that, against the backdrop of European integration processes, the transport systems of the EU countries and Ukraine began to quickly converge, which created the need to study potential innovations in the transport industry and identify the most problematic regions and modes of transport. There is also a constant increase in demand for multimodal transport, especially cross-border transport, and their implementation requires information on the current state of transport systems in countries involved in multimodal transport. Implementation of innovations is necessary to ensure multimodality. The study used statistics from 2012 to 2021, publicly available from Eurostat. Based on the study results, it is possible to determine in which countries the demand for innovation marketing is expected. That is, the study will be useful to specialists in developing and promoting innovations as an overview of the market of potential consumers of this service.
Маркетинговий аналіз динаміки мультимодальних перевезень в логістичній інфраструктурі.